Role of H2O2 in the oxidative effects of zinc exposure in human airway epithelial cells - Phillip A. Wages; Robert Silbajoris; Adam Speen; Luisa Brighton; Andres Henriquez; Haiyan Tong; Philip A. Bromberg; Steven O. Simmons; James M. Samet (Redox Biology, 2014)
Human exposure to particulate matter (PM) is a global environmental health concern. Zinc (Zn2+) is a ubiquitous respiratory toxicant that has been associated with PM health effects. However, the molecular mechanism of Zn2+ toxicity is not fully understood. H2O2 and Zn2+ have been shown to mediate signaling leading to adverse cellular responses in the lung and we have previously demonstrated Zn2+ to cause cellular H2O2 production. To determine the role of Zn2+-induced H2O2 production in the human airway epithelial cell response to Zn2+ exposure. BEAS-2B cells expressing the redox-sensitive fluorogenic sensors HyPer (H2O2) or roGFP2 (EGSH) in the cytosol or mitochondria were exposed to 50 µM Zn2+ for 5 min in the presence of 1 µM of the zinc ionophore pyrithione. Intracellular H2O2 levels were modulated using catalase expression either targeted to the cytosol or ectopically to the mitochondria. HO-1 mRNA expression was measured as a downstream marker of response to oxidative stress induced by Zn2+ exposure. Both cytosolic catalase overexpression and ectopic catalase expression in mitochondria were effective in ablating Zn2+-induced elevations in H2O2. Compartment-directed catalase expression blunted Zn2+-induced elevations in cytosolic EGSH and the increased expression of HO-1 mRNA levels. Zn2+ leads to multiple oxidative effects that are exerted through H2O2-dependent and independent mechanisms.